Discovery of pyrazolopyrrolidinones as potent, broad-spectrum inhibitors of Leishmania infection - Kavouris, John A.; McCall, Laura-Isobel; Giardini, Miriam A.; De Muylder, Geraldine; Thomas, Diane; Garcia-Pérez, Adolfo; Cantizani, Juan; Cotillo, Ignacio; Fiandor, Jose M.; McKerrow, James H.; De Oliveira, Camila I.; Siqueira-Neto, Jair L.; et al. (Frontiers in Tropical Diseases, 2023)
Introduction Leishmaniasis is a parasitic disease that affects more than 1 million people worldwide annually, predominantly in resource-limited settings. The challenge in compound development is to exhibit potent activity against the intracellular stage of the parasite (the stage present in the mammalian host) without harming the infected host cells. We have identified a compound series (pyrazolopyrrolidinones) active against the intracellular parasites of Leishmania donovani and L. major; the causative agents of visceral and cutaneous leishmaniasis in the Old World, respectively. Methods In this study, we performed medicinal chemistry on a newly-discovered antileishmanial chemotype, with over 100 analogs tested. Studies included assessments of antileishmanial potency, toxicity towards host cells, and in vitro ADME screening of key drug properties. Results and discussion Members of the series showed high potency against the deadliest form, visceral leishmaniasis (approximate EC50 ≥ 0.01 µM without harming the host macrophage up to 10.0 µM). In comparison, the most efficient monotherapy treatment for visceral leishmaniasis is amphotericin B, which presents similar activity in the same assay (EC50 = 0.2 µM) while being cytotoxic to the host cell at 5.0 µM. Continued development of this compound series with the Discovery Partnership with Academia (DPAc) program at the GlaxoSmithKline Diseases of the Developing World (GSK DDW) laboratories found that the compounds passed all of GSK’s criteria to be defined as a potential lead drug series for leishmaniasis. Conclusion Here, we describe preliminary structure-activity relationships for antileishmanial pyrazolopyrrolidinones, and our progress towards the identification of candidates for future in vivo assays in models of visceral and cutaneous leishmaniasis.